Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0052785
|View full text |Cite
|
Sign up to set email alerts
|

Production of Functional Soluble Dectin-1 Glycoprotein Using an IRES-Linked Destabilized-Dihydrofolate Reductase Expression Vector

Abstract: Dectin-1 (CLEC7A) is a C-type lectin receptor that binds to β-glucans found in fungal cell walls to act as a major pattern recognition receptor (PRR). Since β-glucans epitope is not present in human cells, we are of the opinion that Dectin-1 can have therapeutic functions against fungal infections. We thus set out to produce a soluble extracellular domain of murine Dectin-1 (called sDectin-1) in sufficient titers to facilitate such studies in mouse models. Since sDectin-1 has previously been shown to be glycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…The authors tested this strategy with the expression of interferon gamma (IFNγ) and found that 1.7‐, 6.6‐ and 13.3‐fold improvements in specific IFNγ productivities were obtained with the application of ARE, MODC PEST, and both ARE and MODC PEST, respectively. In an attempt to more closely link the gene of interest and selection marker (thereby preventing the possibility of gene fragmentation and loss of the target gene), Lam and colleagues introduced the dhfr gene directly downstream of the gene of interest using an Internal Ribosome Entry Sequence (IRES) [89]. This strategy allowed for both genes to be translated off of the same RNA; in addition, the stringency of selection was further increased by adding the PEST sequence to the dhfr gene.…”
Section: Advances In Selection Methodologymentioning
confidence: 99%
“…The authors tested this strategy with the expression of interferon gamma (IFNγ) and found that 1.7‐, 6.6‐ and 13.3‐fold improvements in specific IFNγ productivities were obtained with the application of ARE, MODC PEST, and both ARE and MODC PEST, respectively. In an attempt to more closely link the gene of interest and selection marker (thereby preventing the possibility of gene fragmentation and loss of the target gene), Lam and colleagues introduced the dhfr gene directly downstream of the gene of interest using an Internal Ribosome Entry Sequence (IRES) [89]. This strategy allowed for both genes to be translated off of the same RNA; in addition, the stringency of selection was further increased by adding the PEST sequence to the dhfr gene.…”
Section: Advances In Selection Methodologymentioning
confidence: 99%
“…This concept has been applied to improve the odds of picking a high producer cell clone even when gene amplification is used [29,34,35,36,37,38]. In a recent study, the application of IRES has also allowed for high recombinant protein production from MTX amplified cell pools, without the need for cloning [39]. …”
Section: Protein Expression Technologiesmentioning
confidence: 99%
“…In addition, the use of AU-rich elements (ARE) and murine ornithine decarboxylase (MODC) PEST region as respective mRNA and protein destabilizing elements have been shown to successfully weaken the selection marker, which results in improvements in recombinant protein productivity using the MTX amplification system [42]. In a follow up study, an attenuated IRES element to reduce the expression of the downstream selection marker gene has also been employed to substitute ARE, resulting in high recombinant protein titers [39]. …”
Section: Protein Expression Technologiesmentioning
confidence: 99%
“…For example, Wu et al used a short hairpin RNA targeted to the DHFR gene to generate recombinant IgG expressing CHO clones and found that this approach improved IgG expression by more than 100% and genomic stability in MTX free culture by 30% . The use of a destabilized‐DHFR selection marker linked to an attenuated IRES element has also been shown to be effective in generating high yielding recombinant CHO cell lines . The use of a codon de‐optimized DHFR selectable marker to improve selection stringency in the presence of MTX has also been shown to result in enhanced expression of recombinant proteins, showing that reducing translational efficiency of DHFR, and hence its expression, can be used to isolate cell lines with improved stringency and higher productivities without multiple and time‐consuming gene amplification steps …”
Section: Introductionmentioning
confidence: 99%